Denkschrift über die Neugestaltung der höheren Mädchenschule - Willms, Emil (Historische Quellen zur Frauenbewegung und Geschlechterproblematik ;, 1906)
An essay on the advantages of the ten-year school for girls with some supplementary training possible; but with the foremost aim of preparing good wives and mothers.